Challenges in Type-1 Diabetes Management during the Conflict in Syria - Alali, Ibrahim; Afandi, Bachar (Journal of Diabetes and Endocrine Practice, 2022)
Background In Syria, a country at war for one decade, medical care has been severely affected by shortages in medications, resources, food, and physicians.Objectives This study reviews the quality of care for patients with type-1 diabetes (T1D) receiving treatment in a private endocrinology service in Raqqa City, Syria.Patients and Method A cross-sectional medical record review for patients with T1D followed-up at a private clinic run by a certified endocrinologist in Raqqa, Syria. All medical records were evaluated for patients' characteristics and multiple diabetes care indicators.Results One hundred and ninety-seven patients with T1D were evaluated; 109 (55.3%) patients were females. The median age of participants was 16 (1.7–42) years, median duration of diabetes was 4 (0–27) years, and mean hemoglobin was A1C, 9.1% (8.7–9.5%). One hundred and twenty-five (63.5%) patients used premixed insulin. Eighty-one (42.4%) patients performed regular self-monitoring of blood glucose (SMBG) at least twice daily. Episodes of hypoglycemia and diabetic ketoacidosis (DKA) were reported in 62.4 and 54.4% of patients, respectively. There were significant correlations between the incidence of DKA and female gender and premixed insulin regimens.Conclusion In this private endocrine practice in Raqqa City, Syria, the majority of patients are treated with premixed insulin. Only a minority have their glycosylated A1c monitored regularly. Our unprivileged population is poorly controlled with increased risk of hypoglycemia and admissions with diabetic ketoacidosis.
Keywords: Syria; type-1 diabetes; diabetes care indicators; A1C; hypoglycemia; insulin treatment; diabetic ketoacidosis; self-monitoring of blood glucose